Kupffer cell activation by different microbial lysates: Toll‐like receptor‐2 plays pivotal role on thromboxane A2 production in mice and humans. Issue 12 (14th July 2020) - Zhang, Jiang; Wieser, Andreas; Lin, Hao; Li, Hanwei; Hu, Moyan; Behrens, Ina‐Kristin; Schiergens, Tobias S.; Gerbes, Alexander L.; Steib, Christian J.
Abstract: Thromboxane (TX) A2 has been identified as an important intrahepatic vasoconstrictor upon Kupffer cell (KC) activation during infections such as spontaneous bacterial peritonitis (SBP). The study aimed to investigate the role of TLRs in the TXA2 increase in liver nonparenchymal cells and their related mechanisms. Here, we identified TLR‐2 as a common pathway for different microbials: microbial lysates including Gram‐positive bacteria, Gram‐negative bacteria, and fungi all increased TXA2 secretion via activation of TLR‐2 in human KCs, accompanied by increased expression and phosphorylation of Myd88‐related pathway. Of all TLR agonists, only TLR‐1, ‐2, and ‐4 agonists increased TXA2 in human KCs. These results were further confirmed by mouse liver nonparenchymal cells. Comparing the effects of TLR‐1, ‐2, and ‐4 antagonists, only TLR‐2 antagonist showed inhibitory effects with all tested microbial lysates. Pretreatment with TLR‐2 antagonist in human KCs blocked the secretion of IL‐10, CXCL‐10, TNF‐α, and IL‐6 induced by Gram‐positive and Gram‐negative bacterial stimulation. IL‐23 and IL‐1β were only induced by Gram‐negative bacteria. Thus, TLR‐2 might be a potential marker and an attractive target for future treatment of patients with SBP. In addition, IL‐23 and IL‐1β might distinguish early between Gram‐positive and Gram‐negative SBP. Abstract : TLR‐2 on the surface of human and mouse Kupffer cells (KCs) can be used as a common pathway for stimulation by Gram‐positive (G+) bacteria, Gram‐negative (G‐) bacteria, and fungi, and to regulate TXA2 secretion by affecting the phosphorylation of Myd88 pathway‐related molecule levels.